Participatory evaluation of Linseed (Linum usitatissimum L.) varieties under farmers training center at Dodola District of West Arsi Zone, Oromia Regional State, Ethiopia - Sintayehu Abebe; Marta Gichamo; Alemu Doda; Birhanu Sime (Open Journal of Plant Science - Peertechz Publications, 2022)
The study was carried out in the Dodola district of West Arsi Zone, Oromia regional state, Ethiopia. The aim of this study was to evaluate the performance and farmers varieties preference of Linseed at Alantu kebele within the Farmers Training Center (FTC) demonstration plot of Dodola district of West Arsi Zone. Along with their management practices under the Farmers Training Center (FTC) field to enhance farmers' knowledge and skill on Linseed production performance. The verities used to demonstrate were, improved Linseed varieties namely Kuma, Yadano, Bekoji-14, Kulumsa-1, Kassa-2, and Local check. According to the results, an average yield of 22qt/ha, 22.4 qt/ha 15.6 qt/ha, 19.2q/ha,13.2q/ha, and 9.2q/ha /was harvested from Kuma, Yadano, Bekoji-14, Kulumsa-1, Kassa-2, and Local check Varieties respectively. Yadano variety had a 143.5 %yield advantage over the local check and Kuma had a 139.1% yield advantage over the local check and the variety Kulumsa-1 had a negative 108.7%% yield advantage over the local check and variety Bekoji-14 had 69.6% over the local check and the variety Kassa-2 had 43.5% yield advantage over the local check. The result of the criteria set by the farmers themselves showed that the varieties Yadano, Kuma, Kulumsa-1, Bekoji-14, Kassa-2, and the Local check ranked 1st,2nd,3rd,4th,5th, and 6th respectively. Based on the result of farmers preference ranking and the yield advantages of the Linseed varieties the tested under FTC met the requirements for the recommendation, Therefore, the Authors conclude that the first three (3) varieties namely Yadano, Kuma, and Kulumsa-1 varieties were recommended for the study areas and other areas with similar agro-ecological conditions in the South eastern districts of West Arsi zone as the first, second and third Linseed varieties options respectively. Whereas the remaining 3 (three) varieties namely Bekoji14, and Kassa-2 including the local variety were not recommended due to low productivity in the study area.